Isolation and Screening of Amylase-producing Fungi from Spoiled Fruits (Journal of Environmental Bioremediation and Toxicology, 2023)
Amylase is the enzyme that is employed in the breakdown of starch into its simpler components. The research was aimed at isolating and screening Aspergillus niger from spoiled fruits for amylase enzyme production. The spoiled fruits utilized in this study were orange, tomato, banana, mango, hot pepper and pineapple, and were taken from fruit sellers in Kasuwar Mata within the Gombe metropolis. Six different fungi were isolated from spoiled fruits and were identified using cultural and morphological characteristics. They were screened on starch agar for amylase production. A. niger isolated from banana produced the biggest zone of hydrolysis (76 mm) on starch agar while A. niger from tomato produced the smallest zone of hydrolysis (38 mm). The result of this research indicates that A. niger from spoiled fruits are capable of producing amylase enzyme which can be utilized for different industrial processes.
Keywords: A. niger; Spoiled fruit; Isolation; Screening; Amylase